Mid-term outcome following second-generation cryoballoon ablation for atrial fibrillation in heart failure patients: effectiveness of single 3-min freeze cryoablation performed in a cohort of patients with reduced left ventricular systolic function. Issue 10 (October 2019) - Maj, Riccardo; Iacopino, Saverio; Ströker, Erwin; Paparella, Gaetano; Coutiño, Hugo-Enrique; Terasawa, Muryo; Varnavas, Varnavas; Salghetti, Francesca; Osório, Thiago; Abugattas, Juan P.; Sieira, Juan; Capulzini, Lucio; et al.
Abstract : Purpose: Currently, information on the mid-term outcome of cryoballoon ablation (CB-A) for drug-resistant atrial fibrillation in patients with reduced left ventricular systolic function is limited. Methods: Thirty-eight consecutive patients with paroxysmal or persistent atrial fibrillation (84.2% male), with median left ventricular ejection fraction of 37.3% were included in our study. All patients underwent the procedure with the 28-mm cryoballoon advance. Results: There were no mayor complications related to the CB-A procedure. Median follow-up was 26.5 ± 13.7 months. The freedom from atrial fibrillation after a blanking period of 3 months was 42.9% in our cohort of patients. During the follow-up period, 13 patients underwent at least a new electrophysiological procedure. After a single procedure, the univariate predictors of clinical recurrence after the blanking period were age and persistent atrial fibrillation. Conclusion: Second-generation CB-A of atrial fibrillation seems feasible and safe in patients with heart failure with reduced ejection fraction and heart failure with mid-range ejection fraction, in terms of complications rate and number of applications per vein. All pulmonary veins could be isolated with the 28-mm cryoballoon advance only.